Analisis Tingkat Kesejahteraan Petani Plasma Kelapa Sawit di Kecamatan Abab - Sari, Fitri Yunda; ,, Lifianthi; Syafutri, Merynda Indriyani (Journal of Integrated Agribusiness, 2024)
The palm oil is one of Indonesia's main export commodities. The statistic data of a premier national estate of 2021-2023 shows palm oil plantations in the provinces of Indonesia. One of the principal producers of the Sumatra palm is the Province of Southern Sumatra. The data for the productivity of palm plantations in the province of southern Sumatra, particularly in Penukal Abab Lematang Ilir (Pali) regency shows significant potential. In 2022, the palm palm productivity in the pali regency was showing good results, especially in Abab district that became a major production. The aim of the study is to determinate the proportion food and non-food expenditures of palm oil and evaluate the welfare rate of palm oil farmers in Abad district Penukal Abab Lematang Ilir Regency. Research methode used is the survey method for collecting primary data from plasma farmers. Secondary data comes from a variety of sources, including statistical central agency, agricultural and palm company services in the region. Research shows that spending on food consumption is likely to be higher than non-food consumption expenses indicating that welfare levels are still not optimal.